2017
DOI: 10.1039/c6ra28495g
|View full text |Cite
|
Sign up to set email alerts
|

One pot synthesis of amine-functionalized and angular-shaped superparamagnetic iron oxide nanoparticles for MR/fluorescence bimodal imaging application

Abstract: Herein, we report the simple preparation of water dispersible angular-shaped amine-functionalized super-paramagnetic iron oxide nanoparticles (A-SPIONs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…The presence of alginate and doxorubicin in samples N52 and N52D was observed by the fine peaks between 1000 and 1600 cm −1 . Similar results were recorded in other studies [6,14] TEM and FESEM images (Figure 5 B-E) showed that the nanoparticles had a uniform size of about 20 nm. N52D nanoparticles with Doxorubicin appeared on the images with a surrounding polymer layer.…”
Section: Dependence Of Fluorescent Spectra On Drug Delivery Processsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of alginate and doxorubicin in samples N52 and N52D was observed by the fine peaks between 1000 and 1600 cm −1 . Similar results were recorded in other studies [6,14] TEM and FESEM images (Figure 5 B-E) showed that the nanoparticles had a uniform size of about 20 nm. N52D nanoparticles with Doxorubicin appeared on the images with a surrounding polymer layer.…”
Section: Dependence Of Fluorescent Spectra On Drug Delivery Processsupporting
confidence: 91%
“…Recently, fluorescent-magnetic nanoparticles have been well investigated for multimodal imaging applications [5,6]. In the studies, the near-infrared fluorescent fluorophore, cyanine 5.5 (Cy5.5), was used for labeling the presence of nanoparticles in cells.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of the particles is of equal importance as size in in vivo applications and has been shown to be altered by the addition of halide ions [ 101 ]. There have also been advancements in solvents, such as the thermostable ionic solvent [P6,6,6,14][Tf2N], which has been shown to be capable of synthesizing quasi spherical magnetite nanoparticles of around 14 nm [ 102 ].…”
Section: Methods For the Synthesis Of Ionpsmentioning
confidence: 99%
“…Such low Ms value is attributed to the diamagnetic contribution of the silica shell, which consists large portion of core-shell nanoparticles 30 . To investigate the MR imaging performance of NF-SIONs, phantom test was conducted following the previously reported method 31 . As plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%